Effect of physical densification on sub-gap density of states in amorphous InGaZnO thin films. (September 2018) - Oh, Hyungon; Cho, Kyoungah; Kim, Sangsig
Abstract: In this study, we investigate the relationship between the physical densification and sub-gap density-of-states (DOS) distribution of a-IGZO films prepared under various deposition pressures. For TFTs with a-IGZO channel films, the field effect mobility increases from 10.9 to 24.8 cm 2 /V·s, and the on-current increases from 1.5 to 20.8 μA as the deposition pressure for the channel films decreases from 7 to 1 mTorr. The sub-gap DOS distributions obtained from the electrical characteristics indicate the changes in the density of accepter-like tail states with deposition pressure. Further, the physical densification of the channel films increases as the deposition pressure decreases. Our study demonstrates that the lower density of accepter-like tail states and the higher physical densification contribute to the improved performance of a-IGZO TFTs. Graphical abstract: Highlights: We fabricate a-IGZO TFTs with different deposition pressure on a plastic substrate. The highest physical density shows the highest field-effect mobility of 24.8 cm 2 /V·s. The higher physical density leads to lower density of accepter-like tail states.